Waste works : vital politics in urban Ghana - Chalfin, Brenda (Duke University Press, 2023)
"Waste Works theorizes urban form and dwelling through the infrastructure of bodily waste and sanitation in Tema, Ghana-specifically public toilets. Constituted outside the central planning processes that shaped the city, these excremental infrastructures reflect collective and individual empowerment through political negotiation across class lines. Although household bathrooms and plumbing are standard in Tema's central districts, the outlying communities still rely on public toilets built at Tema's mid-20th-century founding. In Tema, Brenda Chalfin finds that waste infrastructure is not a hidden substrate of the city, but a matter of active debate and construction, and often at the boundary between private interest and public good. Chalfin weaves together theories of power from Hannah Arendt, George Bataille, and Bruno Latour to develop the "vital politics of infrastructure," the inherent instability of political ordering in the face of the vital materials of human bodies"--